{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

Dynamics_Part10

# 5

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: .............. ................................................... ...................................................... .... ... ... . . .. .. ... ... ..... ................................................. . . ... .... .. .. .. ... . ................................................ ............................................. ............................................ .......................................... . . . . . . ... .... ........................................ ................................... ..................................... .... . .. .. ... ... . ............................. ................................ .............................. ........................... ......................... . .. ... ..... ....................... ... .... ................... .................... 2 ................ .............. ............ .......... ........ .. .. . ..... v=V i x g = -g k So ut on: Because we gnore fr c on he mo on of he sk umper s sub ec on y o he cons an grav aona acce era on Deno ng me by t and e ng t = 0 when he sk umper aunches from he op of he s ope he equa ons and n a cond ons govern ng he mo on are d x =0 dt2 x(0) = 0 and x(0) = V d2 z = -g z(0) = 0 and z(0) = 0 dt2 (a) In egra ng w ce and mpos ng he n a cond ons he so u on o he equa ons for x and z s x(t) = V t When he sk umper ands a and 1 z(t) = - gt2 2 me we know ha x( ) = cos and z( ) = - s n = cos V 2 Therefore we have V = cos and 1 1 - s n = - g 2 = - g 2 2 cos V =...
View Full Document

{[ snackBarMessage ]}